Development and optimization of a biological protocol for DNA detection of escherichia coli O157:H7 by quartz crystal microbalance (QCM) - Rodrigues, Raquel Oliveira (2014)
Escherichia coli O157:H7 is a foodborne pathogen associated to outbreaks with high mortality. Since the traditional methods for its detection are often time-consuming, there is a need to develop new techniques that allow a rapid, simple, reliable, specific and sensitive detection. The present study aimed to develop a biological protocol for DNA detection of E. coli O157:H7 using a Quartz Crystal Microbalance with Dissipation (QCM-D), to be applied as a genosensor based on the evaluation of the immobilization/hybridization mass phenomena. Since genosensors use immobilized DNA single strands to detect the complementary sequence by hybridization, it is very important to optimize the conditions used during probe immobilization and target hybridization. In this study, several parameters (concentration, incubation time and temperature) were studied and optimized, on the steps of DNA thiol Probes immobilization, 6-Mercapto-1-hexanol (MCH) blocking agent deposition and DNA Target hybridization. Additionally, both the DNA probe and target oligonucleotides were linked to fluorochromes allowing the use of Epifluorescence microscopy, to verify the mass deposition results obtained by the QCM-D device, in the gold electrode.